Within the context of sociological criticism theory, a literary work from the 17th century; Nefhatü’l-Ezhâr - Kuzubas, Muhammet (Technium Social Sciences Journal, 2020)
Spanning over a period of six centuries from the 13th century till the 19th century, Classical Turkish Literature takes up a reputed position in Oriental Literature. In the earliest centuries, classical Turkish literature was heavily influenced by Arabic and Persian Literature; however upon completing its foundation, it started to embrace a domestic and national character as of 16th century. With the advent of 16th century, particularly in masnavis as used to narrate lengthy stories, a different path was taken from other Oriental literatures in regards to characters and settings in stories. Stories, then, began to evolve within the borders of Ottoman territory and a wider place was reserved to take notice of witnessed problems. In some of these masnavis it is feasible to come across social reflections on the specific period and certain expressions that would most probably not approved at an age this work was compiled. In that sense one of the salient examples is Nefhatü’l-Ezhâr masnavi written by 17th - century poet Nev’i-zâde Atâyî. In Nefhatü’l-Ezhâr it is detected that defects that the poet witnesses in his society are narrated to his readers in short stories that develop within a plot. In such stories, Atâyî criticizes the kind of people exploiting religion for personal gains and those simple men licking powerful men's shoes for self-interest. In relation to social criticism stealing and injustice of rulers are highlighted-issues by the poet. Further to that, by narrating obscene stories, the poet attempts to unveil a form of corruption that has eroded moral fiber of community. In order to better grasp a literary text and locate the author's messages aimed for the reader, there is need to approach a work from a wide range of perspectives. In our research, stories that are considered to reflect traces from society in the said work of Nev’i-zâde Atâyî will be elaborated within the context of sociological criticism.